Influence of induction practices on service delivery by newly employed teachers in primary schools. - Otele, Wesonga, Eugene Pancras. (JOOUST, 2022)
Globally,studies have affirmed that newly employed teachers require meaningful support during their first year of service in the development of professional identity and construction of professional practice. The support begins at teacher induction when newly employed teachers are introduced to the culture of a school .Conversely teaching profession has changed much over the past years and students learn differently hence teachers require more sustenance than ever before to ensure they are successful in the classroom. Survey done in Butula Sub-County pointed out fluctuating and deteriorating standards in education ,low transition in schooling due to unknown factors in the cited years .As a result of these.the following were manifested : Un-expected transfers, low work performance, disciplinary cases, desertion of duty ,leaving the profession and truancy that caused distortion. Despite all previous studies on induction and their recommendations to boost quality teaching ,the problem of limited and unstructured induction for newly employed teachers continues to threaten effective teaching .The purpose of this study was to determine the influence of induction practices on service delivery by newly employed teachers in Public Primary Schools in Kenya.This study was anchored on Construtivist Theory by Vygotsky (1980) and was conducted in Butula Sub-County which was purposively selected due to low learning outcomes as compared to other neigbhouring Sub- Counties.The study was guided by the following objectives: to determine the influence of orientation on service delivery by newly employed teachers in Public Primary Schools ; to assess the influence of mentoring on service delivery by newly employed teachers in Public Primary Schools; to examine the influence of seminars on service delivery by newly employed teachers in Public Primary Schools and : to investigate the influence of workshops on service delivery by newly employed teachers in Public Primary Schools . Concurrent triangulation design was used in this study with a study population of 676 serving teachers from 62 Public Primary schools,62 Deputy HeadTeachers,62 HeadTeachers, 3 Curriculum Support Officers, 1 Sub• County Quality Assurance and Standards Officer and I Sub-County Director of Education in Butula Sub-County giving a total of 805 respondents . The study adopted simple random and purposive sampling to sample 324 respondents representing 40.2 % of the target population . Data collection included the use of questionnaires, interview schedule and document analysis guide.Cronbach's Alpha and Pearson'correlation were used to determine reliability of instruments .Quantitative data was analyzed using descriptive and inferential statistics, while Qualitative data was analyzed on the basis of themes and sub-themes from the study Data was presented in Tables and bar graphs . The following emerged from the study: Pearson's correlation revealed highly positive significant correlations between,orientation,(n=239,r=.936,p<0.05),mentoring(n=239,r=.894p<0.05),seminars,(n=23 9,r=.846,p<0.05) workshops,( (n=239,r=.879,p < 0.05) and service delivery.A comprehensive nation-wide induction program that may accelerate novice teacher efficacy and consequently learner achievement is adopted. This study is significant for a number of reasons. First, the findings of the study are expected to be useful in quality teacher management programs in Kenya. Second,the study may contribute to the existing knowledge and theory on induction of newly employed teachers by revealing areas of deficiency in teacher education.Third, the study provides insight on the need to review new teacher induction programs to reflect teacher improvement programs which ultimately focus on service delivery .
Keywords: Induction practices on service delivery.; Employed teachers in primary schools.; Influence of induction practices on service delivery .; Kenya.